2018
DOI: 10.1108/sajbs-02-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of labelled information and sensory attributes on consumers’ intention to purchase milk

Abstract: Purpose The purpose of this paper is to examine the influences of consumer perceptions of labelled information and sensory attributes on consumers’ intention to buy fresh milk. Design/methodology/approach An experiment was conducted on 117 consumers in a lab at a university. After closely inspecting the labels’ information and tasting two types of milk, participants were asked to fill in a questionnaire, using the direct interview method. Exploratory factor analysis, confirmatory factor analysis and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
0
19
1
Order By: Relevance
“…Therefore, an indirect effect of health consciousness on purchase intent through perceived knowledge indicates that they are purchasing liquid milk against their willingness to buy. Evidence shows that the sensory perceptions of liquid milk can mediate the relationship between perceived knowledge and consumers’ purchase intent [ 109 ]. Thus, perceived barriers influence consumers’ attitude negatively [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, an indirect effect of health consciousness on purchase intent through perceived knowledge indicates that they are purchasing liquid milk against their willingness to buy. Evidence shows that the sensory perceptions of liquid milk can mediate the relationship between perceived knowledge and consumers’ purchase intent [ 109 ]. Thus, perceived barriers influence consumers’ attitude negatively [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the marketers should focus on consumers’ knowledge about LM. Because the perceived knowledge of milk, like ‘taking responsibility for one’s health’, is the key to liquid milk commercialization [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trust in information sources also helps to mediate the relationship between consumers' perceived knowledge and their attitude. The evidence revealed that the market for liquid milk is growing and that it is important for producers to satisfy consumer expectations by ensuring trusted information sources like food labels (e.g., sustainability), because food labels help consumers to mediate the association between attitudes and preferences [111,112].…”
Section: Discussionmentioning
confidence: 99%